Proceedings Visualization '98 (Cat. No.98CB36276)
DOI: 10.1109/visual.1998.745315
|View full text |Cite
|
Sign up to set email alerts
|

Simplification of tetrahedral meshes

Abstract: We present a method for the construction of multiple levels of tetrahedral meshes approximating a trivariate function at different levels of detail. Starting with an initial, high-resolution triangulation of a three-dimensional region, we construct coarser representation levels by collapsing tetrahedra. Each triangulation defines a linear spline function, where the function values associated with the vertices are the spline coefficients. Based on predicted errors, we collapse tetrahedron in the grid that do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…Trotts et al [10] method for decimation of tetrahedral meshes is most similar to ours. Their algorithm computes a local error metric to assign priorities to tetrahedra.…”
Section: Volume Simplificationsupporting
confidence: 60%
“…Trotts et al [10] method for decimation of tetrahedral meshes is most similar to ours. Their algorithm computes a local error metric to assign priorities to tetrahedra.…”
Section: Volume Simplificationsupporting
confidence: 60%
“…These operations are used to simplify tetrahedral meshes. See [32] for a detailed description of the operation. We use bottom-up incidences for all algorithms, whereas for the subdivision algorithms we test different variants: With bottom-up incidences enabled and with only a subset of the bottom-up incidences enabled (those necessary for the computations).…”
Section: Computational Costsmentioning
confidence: 99%
“…Van Gelder et al [1999] implemented vertex removal via half-edge contractions and suggested a local density metric to guide the selection of vertices to remove. Trotts et al [1998;1999], Cignoni et al [2000], and Chopra and Meyer [2002] have all developed contraction-based simplification algorithms. Trotts et al propose an error metric that provides a conservative bound on the maximum deviation of the data field.…”
Section: Related Workmentioning
confidence: 99%